Simian Virus 40 DNA Sequences in DNA of Healthy Adult Mice Derived from Preimplantation Blastocysts Injected with Viral DNA - Jaenisch, Rudolf (1974)
Explanted mouse blastocysts were microinjected in the blastocoel cavity with simian virus 40 (SV40) viral DNA. After surgical transfer to the uteri of pseudopregnant surrogate mothers, approximately 40% of the blastocysts developed to term and became healthy adults without apparent tumors at 1 year of age. Molecular hybridization tests for the presence of SV40-specific DNA sequences were conducted on DNA extracted from various organs of these animals. Between 0.5 and 13 SV40 genome equivalents per diploid mouse DNA value were found in some organs of approximately 40% of the adult survivors; this represents a substantial augmentation of the amount administered per embryo. The results are consistent with the working hypothesis that the SV40 DNA may have been integrated into the host genome; alternatively, the viral DNA may have replicated as an extrachromosomal entity or by lytic infection in a few permissive cells. Persistence of the viral DNA from preimplantation stages to adult life may thus provide a new tool for experimental investigation of vertical transmission and expression of tumor viruses.